Selective Nanoscale Mass Transport across Atomically Thin Single Crystalline Graphene Membranes. Issue 19 (17th March 2017) - Kidambi, Piran R.; Boutilier, Michael S. H.; Wang, Luda; Jang, Doojoon; Kim, Jeehwan; Karnik, Rohit
Abstract : Atomically thin single crystals, without grain boundaries and associated defect clusters, represent ideal systems to study and understand intrinsic defects in materials, but probing them collectively over large area remains nontrivial. In this study, the authors probe nanoscale mass transport across large‐area (≈0.2 cm 2 ) single‐crystalline graphene membranes. A novel, polymer‐free picture frame assisted technique, coupled with a stress‐inducing nickel layer is used to transfer single crystalline graphene grown on silicon carbide substrates to flexible polycarbonate track etched supports with well‐defined cylindrical ≈200 nm pores. Diffusion‐driven flow shows selective transport of ≈0.66 nm hydrated K + and Cl − ions over ≈1 nm sized small molecules, indicating the presence of selective sub‐nanometer to nanometer sized defects. This work presents a framework to test the barrier properties and intrinsic quality of atomically thin materials at the sub‐nanometer to nanometer scale over technologically relevant large areas, and suggests the potential use of intrinsic defects in atomically thin materials for molecular separations or desalting. Abstract : Nanoscale mass transport across atomically thin large‐area single‐crystalline graphene membranes is probed. Selective transport of sub‐nanometer sized ions over nanometer sized molecules indicates the presence of sub‐nanometer to nanometer sized intrinsic defects. This work presents a framework to test intrinsic quality of atomically thin materials over large areas and suggests the potential use of intrinsic defects in atomically thin materials for molecular separations or desalting.